An anionic defensin from Plutella xylostella with potential activity against Bacillus thuringiensis. Issue 6 (22nd July 2016) - Xu, X.-X.; Zhang, Y.-Q.; Freed, S.; Yu, J.; Gao, Y.-F.; Wang, S.; Ouyang, L.-N.; Ju, W.-Y.; Jin, F.-L.
Abstract: Insect defensins, are cationic peptides that play an important role in immunity against microbial infection. In the present study, an anionic defensin from Plutella xylostella, (designated as Px Def ) was first cloned and characterized. Amino acid sequence analysis showed that the mature peptide owned characteristic six-cysteine motifs with predicted isoelectric point of 5.57, indicating an anionic defensin. Quantitative real-time polymerase chain reaction analysis showed that Px Def was significantly induced in epidermis, fat body, midgut and hemocytes after injection of heat-inactivated Bacillus thuringiensis, while such an induction was delayed by the injection of live B. thuringiensis in the 4th instar larvae of P. xylostella . Knocking down the expression of nuclear transcription factor Dorsal in P. xylostella by RNA interference significantly decreased the mRNA level of Px Def, and increased the sensitivity of P. xylostella larvae to the infection by live B. thuringiensis. The purified recombinant mature peptide (PxDef) showed higher activity against Gram-positive bacteria, with the minimum inhibition concentrations of 1.6 and 2.6 µM against B. thuringiensis and Bacillus subtilis, respectively. To our knowledge, this is the first report about an anionic Px Def, which may play an important role in the immune system of P. xylostella against B. thuringiensis.